Medicine Balls : Consultations with the World's Greatest TV Doctor. - Hammond, Phil (Black & White Publishing, 2008)
The world is full of TV doctors, but only Dr Phil has appeared on Have I Got News For You seven times and Countdown nineteen times, a true mark of greatness (whatever Lord Winston says). He is also Private Eye's medical correspondent and possibly the only comic to have appeared at a Public Inquiry. Dr Phil (46, Capricorn) has worked in the NHS for twenty years but only used it twice. He takes no drugs (apart from Australian Shiraz) and has never knowingly been Rolfed. So how does he remain so healthy? And what sort of Doctor is he? Here, at last, are transcripts of his most life-enhancing cons.